False Prolongation of Activated Partial Thromboplastin Time with Aminoglycoside Antimicrobial Agents: A Case Report - Doi, Hiroki; Osawa, Michiko; Ozaki, Ayane; Sato, Seiko; Fujita, Takashi; Akiyama, Hidehiko; Ito, Hiroyasu (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Activated partial thromboplastin time (APTT) is a clotting time assay for screening bleeding tendency, evaluating coagulation factor production capacity, assessing preoperatively, monitoring anticoagulant drugs, and searching for blood coagulation abnormalities such as hemophilia and antiphospholipid syndrome. CASE PRESENTATION: Here, we present a 77-year-old male patient with dyspnea who was suspected to have a drug-resistant Pseudomonas aeruginosa infection and pulmonary mycosis. The patient had no history of bleeding tendencies or anticoagulant medication use. The laboratory test results revealed an abnormally prolonged activated partial thromboplastin time (APTT) of 120.3 s using the Coagpia® APTT-N reagent. The APTT test is frequently used to evaluate blood clotting function and assess for bleeding disorders. Prolonged APTT can indicate coagulation factor deficiencies or the presence of certain conditions such as von Willebr and disease, hemophilia, and disseminated intravascular syndrome. However, APTT standardization has not been achieved, causing discrepancies in test results due to variations in the reagents used. The prolonged APTT, in this case, was initially suspected to be caused by contamination or other artifacts, but repeat blood collections and cross-mixing tests revealed the Coagpia® APTT-N reagent as the cause of false prolongation. The reagent was changed to HemosIL SynthASil APTT, which revealed a normal APTT result. The patient had been receiving the aminoglycoside antimicrobial agent tobramycin, and the blood sample taken at the peak tobramycin level demonstrated the longest APTT time. The APTT shortened over time, corresponding to the decrease in tobramycin blood levels. CONCLUSION: Overall, this paper reports a case of false APTT prolongation due to a specific APTT reagent in the presence of aminoglycoside antimicrobial agents. The findings underscore the difficulties in standar PTT testing and the importance of considering reagent performance characteristics in result interpretations.